Role of the lateral preoptic area in cardiovascular and neuroendocrine responses to acute restraint stress in rats - Duarte, Josiane O. [UNESP]; Gomes, Karina S. [UNESP]; Nunes-de-Souza, Ricardo L. [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2017)
The lateral preoptic area (LPO) is connected with limbic structures involved in physiological and behavioral responses to stress. Accordingly, exposure to stressors stimuli activates neurons within the LPO. In spite of these evidence, an involvement of the LPO on cardiovascular and neuroendocrine adjustments during aversive threats has not yet been investigated. Therefore, in the present study we tested the hypothesis that the LPO is involved in the control of cardiovascular and neuroendocrine responses to acute restraint stress in rats. Bilateral microinjection of the nonselective synaptic blocker CoCl2 (0.1 nmol/100 nl) into the LPO did not affect basal values of either arterial pressure, heart rate, tail skin temperature, or plasma corticosterone concentration. However, LPO treatment with CoCl2 enhanced the tachycardiac response and the increase in plasma corticosterone concentration caused by restraint stress. Conversely, LPO synaptic blockade decreased restraint-evoked pressor response. Sympathetic-mediated cutaneous vasoconstriction during restraint stress was not affected by LPO pharmacological treatment. These findings indicate an inhibitory influence of LPO on tachycardiac and plasma corticosterone responses evoked during aversive threats. Additionally, data suggest that LPO plays a facilitatory influence on stress-evoked pressor response.
Keywords: Blood pressure; Corticosterone; Heart rate; HPA axis; Hypothalamus; LPO; Stress